2021
DOI: 10.3390/jpm11050343
|View full text |Cite
|
Sign up to set email alerts
|

Predicting in-Hospital Mortality of Patients with COVID-19 Using Machine Learning Techniques

Abstract: The present work aims to identify the predictors of COVID-19 in-hospital mortality testing a set of Machine Learning Techniques (MLTs), comparing their ability to predict the outcome of interest. The model with the best performance will be used to identify in-hospital mortality predictors and to build an in-hospital mortality prediction tool. The study involved patients with COVID-19, proved by PCR test, admitted to the “Ospedali Riuniti Padova Sud” COVID-19 referral center in the Veneto region, Italy. The alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…A total of 19/24 studies adopted binary features [20][21][22][24][25][26][27][30][31][32][33][34][35][36][37][38][40][41][42][43]]. 1/24 study dichotomized continuous feature's value in a binary form [28].…”
Section: Class Of Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 19/24 studies adopted binary features [20][21][22][24][25][26][27][30][31][32][33][34][35][36][37][38][40][41][42][43]]. 1/24 study dichotomized continuous feature's value in a binary form [28].…”
Section: Class Of Featuresmentioning
confidence: 99%
“…A total of 6/24 papers [20,23,29,34,42,43] used a Support vector machine (SVM) for mortality prediction, a nonlinear statistical data supervised ML tool that achieved high performance in survival prediction tasks [3,47]. Subudhi et al used Support Vector Classifier (SVC), a linear supervised ML algorithm [40].…”
Section: Classifiersmentioning
confidence: 99%
“…For example, the gradient boosting (GB) model showed the highest ROC (0.79 (0.77–0.80)) for the 30-day mortality prediction in mechanically ventilated patients, followed by the random forest model (0.78 (0.76–0.80)). Other studies conducted to predict the ICU mortality outcome in COVID−19 patients confirmed that the random forest model, followed by the GB predictive tool, outperformed the other MLTs [ 37 ]. Furthermore, the XGB model performs better, in comparison with the other MLTs, in predicting the adverse outcome of critically ill influenza patients admitted to the ICU [ 38 ].…”
Section: Discussionmentioning
confidence: 92%
“…The CT data of 674 patients from six hospitals in northern Italy were used to extract pulmonary parenchymal and vascular features. While machine learning models centered on clinical and imaging data have been proposed to aid both COVID-19 diagnosis and severity stratification [55][56][57][58][59], the inclusion of vascular features stems from an ever-larger corpus of observations that link vascular (particularly endothelial) impairment in COVID-19 [4][5][6][7][8][9] to pulmonary thromboembolism [11][12][13][16][17][18][19][20]23] and gross damage to pulmonary arterial vessels [25][26][27].…”
Section: Discussionmentioning
confidence: 99%